Obstetric anal sphincter injury, risk factors and method of delivery – an 8-year analysis across two tertiary referral centers. (October 2013) - Hehir, Mark P.; O'Connor, Hugh D.; Higgins, Shane; Robson, Michael S.; McAuliffe, Fionnuala M.; Boylan, Peter C.; Malone, Fergal D.; Mahony, Rhona
Abstract Objective: Obstetric anal sphincter injury (OASIS) represents a major cause of maternal morbidity and is a risk factor for the development of fecal incontinence. We set out to analyze the incidence of OASIS and its association with mode of delivery in two large obstetric hospitals across an 8-year study period. Methods: This was a prospective observational study carried out at two large tertiary referral centers serving a single urban population, from 2003 to 2010. Incidence of OASIS was examined as well as the influence of parity and mode of delivery on the occurrence of OASIS. Results: During the study period, there were 100 307 vaginal deliveries at the two hospitals. There was a total of 2121 cases of OASIS from 2003 to 2010, giving an incidence of 2.1% of vaginal deliveries. Patients were more likely to suffer an OASIS when having a forceps delivery than when having a normal vaginal delivery (8.6% versus 1.3%, p < 0.0001, OR: 7.1, CI: 6.4–7.9). Vacuum delivery also carried an increased risk of sphincter injury compared with normal delivery (3.7% versus 1.3%, p < 0.0001, OR: 2.9, CI: 2–2.6). About 16.7% of infants delivered were macrosomic (birthweight > 4 kg). The rate of episiotomy during the study was 19.1%. Conclusion: These results demonstrate that OASIS remains an important cause of maternal morbidity in contemporary obstetric practice. These results will likely be of value in risk management planning and patient debriefing in what is a highly litigious area of obstetrics.